2017
DOI: 10.1007/s10035-017-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Scale separation between grain detachment and grain transport in granular media subjected to an internal flow

Abstract: Based on a discrete element method (DEM), this paper investigates the basic mechanisms and the associated scales related to grain detachment and grain transport processes at stake in widely graded poly-disperse assemblies of spheres subjected to internal fluid flows. From the identification of force chains, particles sensitive to grain detachment are identified. Based on the computation of autocorrelation lengths, a typical length scale associated with this phenomenon is then defined. From the characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Thanks to the combine use of photoelastic grains and numerical simulations, the overall behavior of granular materials was shown to rely on a limited number of grains organized in mesostructures called force chains . Following the definition as well as the algorithm given in Peters et al, recent results highlighted the importance of these mesoscale structures with respect to the overall mechanical properties of the granular materials . In particular, it has been shown that the strength of a granular material results from its ability to build relatively long force chains and its ability to constantly rearrange existing ones to cope with any change in the boundary conditions.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Thanks to the combine use of photoelastic grains and numerical simulations, the overall behavior of granular materials was shown to rely on a limited number of grains organized in mesostructures called force chains . Following the definition as well as the algorithm given in Peters et al, recent results highlighted the importance of these mesoscale structures with respect to the overall mechanical properties of the granular materials . In particular, it has been shown that the strength of a granular material results from its ability to build relatively long force chains and its ability to constantly rearrange existing ones to cope with any change in the boundary conditions.…”
Section: Introductionmentioning
confidence: 74%
“…Now commonly used in the literature, the force chain concept provides a relevant mesoscopic scale to account for the macroscopic mechanical behavior of granular materials . In particular, it has been shown that the strength of a granular material results from its ability to build relatively long force chains and to constantly rearrange the existing force chains to cope with any change in the boundary conditions .…”
Section: Micromechanical Analysis Of the Onset And Development Of Insmentioning
confidence: 99%
See 3 more Smart Citations